Potential biodegradation of Tapis Light Crude Petroleum Oil, using palm oil mill effluent final discharge as biostimulant for isolated halotolerant Bacillus strains - Sayed, K. (Elsevier Ltd, 2021)
Petroleum hydrocarbon pollution in marine waters has been an extremely significant environmental and health issue worldwide. This study aims at constructing an efficient indigenous bacterial consortium to biodegrade Tapis Light Crude Petroleum Oil (TLCO). The local agro-industrial wastewater of palm oil mill effluent final discharge (POME FD) was used as biostimulant to enhance the biodegradation efficiency. In this study, three TLCO degrading bacteria were isolated from seawater samples collected. Molecular identification using 16S rRNA genes sequencing was done and results show that these isolated strains belong to: Bacillus tropicus, Bacillus licheniformis and Bacillus subtilis. Bacterial consortium tested using four different concentrations of POME FD (0.1, 0.25, 0.5, and 1) as biostimulant and TLCO (0.5 and 1.0) degradation capability was investigated. The residual TLCO in culture medium after 40 days was analysed. The results confirmed that POME FD dosage of 0.25 is optimum for the bacterial consortium and can degrade 99.85 of TLCO at 0.5. However, TLCO degradation with POME FD dosage (0.25) in TLCO (1.0) was found optimum, with biodegradation reaching up to 95.23 in 40 days. This study is a beginning for the future development of a consortium of petroleum hydrocarbon degrading bacteria to mitigate oil spills in the Malaysian shoreline. Â© 2021 Elsevier Ltd